Fatigue in Medical Residents – Lessons to be learned / Affaticamento fra medici interni israeliani: una lezione da apprendere - Fruchtman, Y.; Moser, A.M.; Perry, Z.H. (La Medicina del Lavoro, 2011)
Summary Background: Fatigue among medical residents is a well-known and widely discussed phenomenon that has generated much debate. Objective: We wanted to evaluate self-reported fatigue and sleep deprivation, as well as some of the major consequences that have been identified in the period after the medical residents’ strike in 2000. Design: A cross sectional study. Participants: Seventy-six medical residents at Soroka university medical centre, who were asked to answer a questionnaire about their personal lives and fatigue level. Data and results: The average work-week was 68.1±12.4 hours. Residents reported 6.0±1.3 hours of sleep per night on a regular day and an average of 1.1±0.5 hours during a 24-hour on-call shift. The ESS score was 11.5±5.4 points. The number of hours worked per week correlated significantly with the ESS score. Of the residents who drove after a night shift, 29.3% reported falling asleep at least once while driving, and 13.9% of drivers reported that they were involved in a motor vehicle accident. Conclusions: In view of these results, we express a deep concern for the future of Israeli medical residents and their patients. We call upon the authorities to develop appropriate working conditions that will ensure the safety of patients and residents